2022
DOI: 10.1038/s41467-022-30293-9
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-mediated higher-order assembly of heterodimers in amino acid transport system b0,+ biogenesis and cystinuria

Abstract: Cystinuria is a genetic disorder characterized by overexcretion of dibasic amino acids and cystine, causing recurrent kidney stones and kidney failure. Mutations of the regulatory glycoprotein rBAT and the amino acid transporter b0,+AT, which constitute system b0,+, are linked to type I and non-type I cystinuria respectively and they exhibit distinct phenotypes due to protein trafficking defects or catalytic inactivation. Here, using electron cryo-microscopy and biochemistry, we discover that Ca2+ mediates hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(140 reference statements)
2
2
0
Order By: Relevance
“…Relevant to this work, smFRET could help to show that the LeuT transporter, a bacterial homolog of the neurotransmitter sodium symporter (NSS) family with APC fold(Yamashita et al , 2005), undergoes a rocking motion and switch from an outward-facing to an inward-facing conformation (Zhao et al , 2010, 2011; Tavoulari et al , 2016; Malinauskaite et al , 2014; Terry et al , 2018; Khan et al , 2020). The proposed rocking motion of the bundle domain (TM1, TM2, TM6 and TM7) versus the scaffold domain (TM3, TM4, TM8 and TM9) between outward-facing to inward-facing conformations is consistent with the general mechanism observed in other members of the APC transporter superfamily, including LAT structures (Errasti-Murugarren et al , 2019; Yan et al , 2019; Lee et al , 2019; Rodriguez et al , 2021; Parker et al , 2021; Yan et al , 2020a; Wu et al , 2020; Lee et al , 2022; Jeckelmann et al , 2022; Yan et al , 2020b, 2021; Lee et al , 2023).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Relevant to this work, smFRET could help to show that the LeuT transporter, a bacterial homolog of the neurotransmitter sodium symporter (NSS) family with APC fold(Yamashita et al , 2005), undergoes a rocking motion and switch from an outward-facing to an inward-facing conformation (Zhao et al , 2010, 2011; Tavoulari et al , 2016; Malinauskaite et al , 2014; Terry et al , 2018; Khan et al , 2020). The proposed rocking motion of the bundle domain (TM1, TM2, TM6 and TM7) versus the scaffold domain (TM3, TM4, TM8 and TM9) between outward-facing to inward-facing conformations is consistent with the general mechanism observed in other members of the APC transporter superfamily, including LAT structures (Errasti-Murugarren et al , 2019; Yan et al , 2019; Lee et al , 2019; Rodriguez et al , 2021; Parker et al , 2021; Yan et al , 2020a; Wu et al , 2020; Lee et al , 2022; Jeckelmann et al , 2022; Yan et al , 2020b, 2021; Lee et al , 2023).…”
Section: Introductionsupporting
confidence: 78%
“…The proposed rocking motion of the bundle domain (TM1, TM2, TM6 and TM7) versus the scaffold domain (TM3, TM4, TM8 and TM9) between outward-facing to inwardfacing conformations is consistent with the general mechanism observed in other members of the APC transporter superfamily, including LAT structures (Errasti-Murugarren et al, 2019;Yan et al, 2019;Lee et al, 2019;Rodriguez et al, 2021;Parker et al, 2021;Yan et al, 2020a;Wu et al, 2020;Lee et al, 2022;Jeckelmann et al, 2022;Yan et al, 2020bYan et al, , 2021Lee et al, 2023).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The semi-occlusion of Asc1 is the result of a partial tilting of TM1a to an intermediate position between the fully open cytosolic gate of human LAT2 21 and the fully occluded cytosolic gate of human LAT1 25 . As a result, the polar contact between the fully conserved lysine residue in the TM5 of LATs (Lys 194; human Asc1 numbering) with a backbone atom in TM1, present in all LAT structures already determined 19 24 , 26 28 , 33 , is not present in the semi-occluded inward-facing conformation of Asc1. Upon complete closing of the cytosolic gate, this conserved lysine residue bridges backbone atoms in TM5 and TM8, as shown in human LAT1 25 and in the Cationic Amino Acid transporter homolog GkApcT 34 , but not in Asc1.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies of bacterial homologs have revealed a LeuTlike fold that mediates alternating access to a central binding site for amino acid transport [27][28][29][30][31] . Understanding of amino acid transport by human SLC7 genes has been further illuminated by recent structures of b 0,+ AT1 [32][33][34] , xCT -35,36 , LAT1 [37][38][39] , and Asc1 40,41 . Structures of AdiC 42 , engineered GkApcT 27 , and B 0,+ AT1 32 have revealed these proteins' interactions with arginine, though the substrate's binding pose and coordination chemistry are quite distinct among the distant homologs.…”
Section: Introductionmentioning
confidence: 99%